2020
DOI: 10.1109/access.2020.3002713
|View full text |Cite
|
Sign up to set email alerts
|

A Distortion-Based Potential Game for Secondary Voltage Control in Micro-Grids

Abstract: In this work, we present a multi-agent learning model based on the maximum entropy (MAXEnt) and the rate distortion function to define, respectively, the environment of the agents and their understanding about it. The avoidance of redundant information under distortion conditions is used to define a distortion-based potential function that is minimized in order to find an equilibrium point in a potential game setting, in which the Lagrange multiplier β, used as input in the Blahut-Arimoto algorithm, determines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Mutual information has gained special attention in recent years in areas such as multi-agent systems [ 17 ], coverage control [ 18 , 19 ], distributed control in micro-grids [ 20 ], and neuroscience [ 15 , 21 ] due to its capability to analyze relationships between data from different contexts (e.g., voltage values, stimulus light position, animal position), the ability to detect linear and nonlinear interactions, and its usage in multivariate systems.…”
Section: Methodsmentioning
confidence: 99%
“…Mutual information has gained special attention in recent years in areas such as multi-agent systems [ 17 ], coverage control [ 18 , 19 ], distributed control in micro-grids [ 20 ], and neuroscience [ 15 , 21 ] due to its capability to analyze relationships between data from different contexts (e.g., voltage values, stimulus light position, animal position), the ability to detect linear and nonlinear interactions, and its usage in multivariate systems.…”
Section: Methodsmentioning
confidence: 99%
“…Ma and Zhang [17] applied an adaptive hierarchical control strategy considering grid stability as a constraint while minimizing the power generation costs in a microgrid with multiple prosumers. Martinez et al [18] proposed a learning-based management approach for a microgrid with competitive agents (i.e., each representing a distributed flexible asset), which improves voltage quality via reactive power-sharing between distributed generators. These studies showed that various control approaches exist to improve power quality in systems similar to LECs.…”
Section: Related Workmentioning
confidence: 99%